1996
DOI: 10.1021/jm960169g
|View full text |Cite
|
Sign up to set email alerts
|

Deconvolution of Combinatorial Libraries for Drug Discovery:  Experimental Comparison of Pooling Strategies

Abstract: An experimental evaluation of several different pooling strategies for combinatorial libraries was conducted using a library of 810 compounds and an enzyme inhibition assay (phospholipase A2). The library contained compounds with varying degrees of activity as well as inactive compounds. The compounds were synthesized in groups of three and pooled together in various formats to realize different pooling strategies. With one exception, all iterative deconvolution strategies and position scanning resulted in ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
2

Year Published

1998
1998
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(34 citation statements)
references
References 20 publications
0
32
0
2
Order By: Relevance
“…Pooled screening methods have been explored to identify enzyme inhibitors 9 and to look for synergistic anti-inflammatory compound pairs 10 although the latter study did not yield novel synergistic compound pairs. Here we develop a pooled screening method named MuSIC ( M ultiplex S creen for I nteracting C ompounds) to screen a large collection of diverse FDA-approved or clinically-tested compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Pooled screening methods have been explored to identify enzyme inhibitors 9 and to look for synergistic anti-inflammatory compound pairs 10 although the latter study did not yield novel synergistic compound pairs. Here we develop a pooled screening method named MuSIC ( M ultiplex S creen for I nteracting C ompounds) to screen a large collection of diverse FDA-approved or clinically-tested compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Although active compounds are identified without iterative synthesis using positional scanning, in comparison with iterative deconvolution there is an increased likelihood that the most potent compound(s) will not be identified [98], [99].…”
Section: Deconvolution By Positional Scanningmentioning
confidence: 99%
“…But the number of split and pool operations that would be required for library synthesis is rather high so that building block mixtures are used in several of the library synthesis steps in order to reduce the number of operations. A thorough examination of the theoretical and experimental aspects of iterative and positional scanning deconvolution has been published [98].…”
Section: Deconvolution By Positional Scanningmentioning
confidence: 99%
“…Different pooling strategies have been experimentally compared using a library of 810 phosphate diester-linked peptide trimers. The results showed that random pooling, positional scanning, and iterative methods identified the same active compound [25]. But applying an artificial procedure where the best compound was hidden in a pool of least active compounds failed to identify the optimal trimer structure [25].…”
Section: Limitations Of Pooled Compound Screening Strategiesmentioning
confidence: 99%
“…The results showed that random pooling, positional scanning, and iterative methods identified the same active compound [25]. But applying an artificial procedure where the best compound was hidden in a pool of least active compounds failed to identify the optimal trimer structure [25]. This is the primary reason behind the drive to miniaturization and increased throughput.…”
Section: Limitations Of Pooled Compound Screening Strategiesmentioning
confidence: 99%